Multiple Intestinal Perforation and Necrosis due to Magnet Ingestion - Sekmenli, Tamer (Eurasian J Med, 2016)
Among the few foreign bodies swallowed, multiple magnets are very rare. Ingestion of Multiple Magnets may lead to a number of dire complications. The present case report is about the ingestion of multiple singing magnets by 4-year-old child leading to intestinal segmental necrosis and perforations.